2012
DOI: 10.1155/2012/278273
|View full text |Cite
|
Sign up to set email alerts
|

Isorhamnetin, A Flavonol Aglycone fromGinkgo bilobaL., Induces Neuronal Differentiation of Cultured PC12 Cells: Potentiating the Effect of Nerve Growth Factor

Abstract: Flavonoids, a group of compounds mainly derived from vegetables and herbal medicines, share a chemical resemblance to estrogen, and indeed some of which have been used as estrogen substitutes. In searching for possible functions of flavonoids, the neuroprotective effect in brain could lead to novel treatment, or prevention, for neurodegenerative diseases. Here, different subclasses of flavonoids were analyzed for its inductive role in neurite outgrowth of cultured PC12 cells. Amongst the tested flavonoids, a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
64
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 73 publications
(68 citation statements)
references
References 30 publications
4
64
0
Order By: Relevance
“…In hippocampus this parameter was significantly increased in the animals treated with conventional grape juice (Figure 1a). Several studies have shown that different polyphenols, including flavonoids such as genistein, quercetin, isorhamnetin (a flavonolaglycone) from Ginkgo biloba plant and acetylated flavonoid glycosides from Scopariadulcis, as well as resveratrol (the stilbenoid compound present in grapes and red wine) cause a significant enhancement of neurotrophin (nerve growth factor [NGF] and brain-derived neurotrophic factor [BDNF])-mediated neurite outgrowth in PC12 cells ( Nakajima et al 2011, Xu et al 2012, Li et al 2004, Zhang et al 2012. Interestingly, in the hippocampus we observed that only the conventional grape juice increased the BDNF level, this result could be explained by the epicatechin level.…”
Section: Resultsmentioning
confidence: 99%
“…In hippocampus this parameter was significantly increased in the animals treated with conventional grape juice (Figure 1a). Several studies have shown that different polyphenols, including flavonoids such as genistein, quercetin, isorhamnetin (a flavonolaglycone) from Ginkgo biloba plant and acetylated flavonoid glycosides from Scopariadulcis, as well as resveratrol (the stilbenoid compound present in grapes and red wine) cause a significant enhancement of neurotrophin (nerve growth factor [NGF] and brain-derived neurotrophic factor [BDNF])-mediated neurite outgrowth in PC12 cells ( Nakajima et al 2011, Xu et al 2012, Li et al 2004, Zhang et al 2012. Interestingly, in the hippocampus we observed that only the conventional grape juice increased the BDNF level, this result could be explained by the epicatechin level.…”
Section: Resultsmentioning
confidence: 99%
“…It also allows the control on the molecular level through the activation of a number of neuronal signaling pathways such as phosphatidylinositol-3 kinase/protein kinase B/Akt, protein kinase C, protein kinase A, Ca-calmodulin kinase, and mitogenactivated protein kinase pathways (Spencer, 2008). Thus, isorhamnetin, one of the sixty-five flavonoids from Ginkgo biloba L. has the best effect on the potentiation of NGF-induced neurite outgrowth and neurofilament expression by inducing the expression of neurofilaments (Xu et al, 2012). These reports mean that isorhamnetin-4′-glucoside and quercetin-4′-glucoside of EOF were better absorption than quercetin and quercetin-4′-glucoside of EOP.…”
Section: Identification Of Main Phenolics With Q-tof Uplc/msmentioning
confidence: 99%
“…Previously, it has been stated that flavonoids could protect the neurons against cell toxicity induced by oxidative stress [16] and by aggregated β -amyloid [17]: these stress inducers are considered as the causes of Alzheimer's disease. In addition, flavonoids were also shown to significantly potentiate NGF-induced neurite outgrowth [18], as demonstrated in cultured PC12 cells. Having a close resemblance to estrogen, the roles of various flavonoids in inducing the expression of neurotrophic factors could be an interesting question.…”
Section: Introductionmentioning
confidence: 99%